2017
DOI: 10.1007/s11356-017-9041-2
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidation of commercial herbicides mixture: experimental design and phytotoxicity evaluation

Abstract: In this work, the suitability of the UV/HO process for commercial herbicides mixture degradation was studied. Glyphosate, the herbicide most widely used in the world, was mixed with other herbicides that have residual activity as 2,4-D and atrazine. Modeling of the process response related to specific operating conditions like initial pH and initial HO to total organic carbon molar ratio was assessed by the response surface methodology (RSM). Results have shown that second-order polynomial regression model cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 55 publications
1
4
0
Order By: Relevance
“…Both studies compared the results obtained from a mathematical model with the experimental ones. Vidal et al reported 80% glyphosate remotion and 70% TOC remotion after 12 treatment hours, these results were similar to the percentage remotion reported by López et al [62].…”
Section: Uv-based Treatment Processsupporting
confidence: 85%
See 1 more Smart Citation
“…Both studies compared the results obtained from a mathematical model with the experimental ones. Vidal et al reported 80% glyphosate remotion and 70% TOC remotion after 12 treatment hours, these results were similar to the percentage remotion reported by López et al [62].…”
Section: Uv-based Treatment Processsupporting
confidence: 85%
“…Furthermore, formaldehyde, formic acid and nitrate, ammonium, and phosphate ions were detected as final degradation products of glyphosate [59]. Other authors as Vidal et al [61] and López et al [62] have studied the H 2 O 2 /UVC system for degradation of commercial glyphosate herbicide mixture in water. Both studies compared the results obtained from a mathematical model with the experimental ones.…”
Section: Uv-based Treatment Processmentioning
confidence: 96%
“…Other authors carried out the same analysis but, unlike those mentioned above, they did it with a mixture of pesticides, also in an aqueous solution. This is the case of López et al (2018), who studied the degradation of pesticides mixture (glyphosate, 2,4-D and atrazine) through the UV/H 2 O 2 process. In this case, an improvement was observed in the conversion to intermediate pH ( 5) with a low R, while with a higher R the improvement was at a pH = 10.…”
Section: Toc Conversionmentioning
confidence: 99%
“…In order to overcome the cost of photocatalyst production, the combination of hydroperoxide and UV radiation (H 2 O 2 /UV) has been reported to treat glyphosate at higher concentrations (up to 90 mg.L −1 ). This process is quite simple and convenient (López et al, 2018;Manassero et al, 2010;Vidal et al, 2015). During H 2 O 2 /UV process, the H 2 O 2 concentration is an important parameter.…”
Section: Advanced Oxidation Processes (Aops)mentioning
confidence: 99%